Effect of chloroquine on different stages of asexual forms of plasmodium falciparum in culture - Zhou Yuan-chang; Guan Wei-bin; Huang Wen-jin; Pan Wei-qing (Acta Pharmacologica Sinica, 2016)
FCC-1/HN strain of Plasmodium falciparum in culture was synchronized with 5% mannitol solution in particular stages to be tested. Each well of plastic plates was filled with 200 vI of culture medium containing 5 v1 of infected and uninfected rbc with or without drug and incubated at 36.5-37 。C by Trager's candle jar method. The whole test consisted of 6 groups (G): G1 and G2 were exposed to chloroquine (CQ) at ring stage (R). G3 and G4 at trophozoite stage (T). and G5 and G6 at schizont stage (S). The final concentrations of CQ were 8. 16. 32 and 64 ng base/ml. Each group had its own control and 4 replicates for each test. G1. G3. G5 and G2, G4. G6 were exposed to CQ for 8 and 48 h. respectively. Parasite count (including normal and abnormal appearances) per 5000 rbc was made on thin blood film at 48 h of culturing (calculated from the commencement of exposure to CQ). The ED60 0f Gl, G3. G5 and their abnormal parasite rate of the parasites after exposure to CQ 32 ng/ml for 8h were 16.9. 23.2. 37.7 ng/ml and 93.1%. 16.2%. 3.4%. respectively. The ED50 of G2. G4. G6, and their abnormal parasite rate after exposure to CQ 16 ng/ml for 48 h were 11.2, 16.4, 17.9 ng/ml and 81.8%, 3%. 0%. respectively. It is suggested that the efficacy of CQ is more remarkable at R stage than at T stage. which. in turn. is more remarkable than at S stage.